2015
DOI: 10.1080/10522158.2015.1005784
|View full text |Cite
|
Sign up to set email alerts
|

Protesting Against Mothers’ Surveillance: Salvadorian Mothers and Their Daughters Negotiating Adolescence in a Foreign Context

Abstract: This article examines how Salvadorian immigrant mothers and their daughters negotiate adolescence in a settlement context that differs from their home country. The author interviewed 42 women, all living in a midsized city in Ontario, Canada: 32 in-depth individual interviews were carried out with Salvadorian-born mothers and, separately, with one of their daughters (either adolescent or adult); and five interviews included mothers and their adolescent or adult daughters together (N = 10). A grounded theory ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…There exists an intrinsic link in the effect that family bonds have in the subsequent placemaking and identity negotiations which take place between parents and children. As Carranza (2015) found in her work with mothers and daughters, there is a balancing act which Salvadoran children must undertake in an attempt to make sense of their relationship with their traditional parents and the new country of reception.…”
Section: Situating the Researchermentioning
confidence: 99%
See 3 more Smart Citations
“…There exists an intrinsic link in the effect that family bonds have in the subsequent placemaking and identity negotiations which take place between parents and children. As Carranza (2015) found in her work with mothers and daughters, there is a balancing act which Salvadoran children must undertake in an attempt to make sense of their relationship with their traditional parents and the new country of reception.…”
Section: Situating the Researchermentioning
confidence: 99%
“…That is not to say that the trauma of the narrative does not impact me. Carranza (2015) argues that refugees' experiences serve as the framework for their meaning-making process and subsequently impact the strategies they use to raise and support their children. Poteet and Simmons (2016) found that Central American youth were often hugely affected by the difficult circumstances under which their parents migrated.…”
Section: Situating the Researchermentioning
confidence: 99%
See 2 more Smart Citations
“…Children are often central to migrants’ decision to migrate, and the education, health and future of their children are of the utmost importance 4 8. Loss of social support networks, experiences of discrimination and racism, a lack of employment and housing, a shift in social status, adapting to a new culture and language, and barriers in accessing education, health and social services, however, can have important effects on the well-being of migrant parents and their children 4 8 12 31–44. Parents face financial constraints, are preoccupied with work and therefore have insufficient time and money for raising their children 4 35 44.…”
Section: Introductionmentioning
confidence: 99%